Stereotypes and Trauma: Germany in John Hawkes’s The Cannibal and Walter Abish’s How German Is It - Theophilus Savvas (European Journal of American Studies)
This article examines the representation of Germany in John Hawkes’s The Cannibal (1949) and Walter Abish’s How German Is It (1979). The two texts are brought together because the fictional versions of Germany they represent are constructed via a calculated employment of stereotyped images of the country. Here, I reconsider this use of stereotype, and discuss the relationship of the two novels with the traumatic events that constitute the background radiation to them. I draw out similarities in the novels’ textual engagement with trauma, stereotype, and narrative stylistics, but also differences – differences which are, in part, the result of the very different contexts, both literary and historical, in which the texts were written. By drawing on Abish’s autobiographical text Double Vision: a Self Portrait (2004) I argue that How German Is It might be profitably read as a “working through” of the author’s own traumatic relationship with his past, which allows me to briefly discuss more generally the role of fiction, memory and trauma.